Pemahaman Konsep Mahasiswa Materi Integral Lipat Dua Melalui Pembelajaran Jarak Jauh Dimasa Pandemi Covid-19 - Utari, Rahma Siska; Andinasari, Andinasari; Gustiningsi, Tria (Program Studi Pendidikan Matematika, Universitas Islam Negeri Raden Fatah Palembang, 2021)
This study aims to determine students' conceptual understanding proficiency of twofold integral material through distance learning during the covid-19. This study use qualitative research with descriptive methods. The students' conceptual understanding proficiency was measured by indicators of concept understanding which consist of: 1) restating a concept, 2) presenting the concept in various forms of mathematical representation, 3) using, utilizing and selecting certain procedures or operations, 4) applying concepts and problem solving algorithms . The distance learning process is implemented using the WhatsApp application, google classroom, and google form. The subjects in this study were 63 students in the fourth semester of the 2019/2020 academic year Mathematics Education Study Program, Faculty of Education and Teacher Training, UIN Raden Fatah Palembang. Data were collected through tests and questionnaires. The data were analyzed by reduction process, data display, and conclusion. The results showed that more than 70% of students understood the concept of twofold integral material through distance learning (PJJ) well, and students’ promblem about concept of twofold integral material which was influenced by internal and external factors that occurred during PJJ.